A Study on Water Resources Management by Water Resources Department in Chhatttisgarh - Franklin, Aashima (International Journal of Computer Sciences and Engineering, 2025)
This paper is focused on water resource management(WRM) with particular reference to responsibility and function of water resource department(WRD) Water is becoming a central issue in this new periods through this paper researcher can make aware common people and asses the possibilities of water resource development in water productivity and to save water is more highlighted .Environment is affected due to growth of population and degrading through uncontrolled expansion of urbanization, industrialization, intensified agricultural activities of human being. In India, due to rapid growth of population and expansion of development activities, environment is adversely affected. India is the second most populous country in the world having over 1.271 billion population (17.5%) of world’s total population determining that how much pressure of the population on environment and natural resources . There are many regions where our freshwater resources are inadequate to meet domestic needs, lack of adequate clean water to meet human drinking water. The role of storage of water by traditional and modern method to increase ground water level for irrigation purpose and solution of water crisis is discussed .From last 5 years, a crisis of water has been recorded in the state, in summer. This paper identifies those problems and try to solve them to create a more sustainable and desirable future. Few suggestions are given to common people through this paper. Data is collected with help of secondary method. Books, newspapers, magazines , journals and websites are used for data